The legacy of the famous Mashkur Zhussup is a value of the Great Steppe - Galymzhanov, Б.Ғ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
This article examines the national values in the heritage of the poet, Shezhire, historian, ethnographer Mashhur-Zhusip, raising the problems of universal values. In order to understand the national values in the works of the poet, study his works and to promote it in accordance with modern requirements that is important for future generations. The article analyzes national values in the heritage of MashhurZhusup, reflecting the significance and significance of national values in the life of mankind. The works of the poet indicate that his works are aimed at purity, constant education and search for their own way, through excperts from the works of the author of the article.